Cost management : strategies for business decisions - Hilton, Ronald W.; Maher, Michael; Selto, Frank H. (Boston, Mass. : McGraw-Hill/Irwin, 2006)
Addresses traditional cost concepts, but makes cost accounting functional by focusing on measuring and managing costs. The real-world approach of this text, including the use of focus companies and the accompanying focus sites, provides a realistic business environment, and aids in student comprehension and interest in the subject.
Includes bibliographical references (p. 887-892) and indexes.
oif 11/11/14
Loan
Keywords: Managerial accounting; Cost accounting; Management accounting